Decarboxylative bromination of α,β-unsaturated carboxylic acids via an anodic oxidation - Bi, Mei-Xiang; Qian, Peng; Wang, Yu-Kang; Zha, Zheng-Gen; Wang, Zhi-Yong (Chinese chemical letters, 2017)
A novel bromination of α,β-unsaturated carboxylic acids was developed via a decarboxylation by virtue of a direct anodic electro-oxidation.In this method,ammonium bromide was employed as a bromine source and the reaction features transition-metal-free,short time,and no additional supporting electrolyte.